2021
DOI: 10.1186/s12870-021-03311-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characteristics and ploidy trigger the high inducibility of double haploid (DH) inducer in Brassica napus

Abstract: Background Our recently reported doubled haploid (DH) induction lines e.g., Y3380 and Y3560 are allo-octoploid (AAAACCCC, 2n = 8× ≈ 76), which can induce the maternal parent to produce DH individuals. Whether this induction process is related to the production of aneuploid gametes form male parent and genetic characteristics of the male parent has not been reported yet. Results Somatic chromosome counts of DH inducer parents, female wax-less parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 98 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…The induced F 1 by interspecies hybridization was obtained by induction selfing through F 1 egg cells [ 21 , 22 ], and there might be changes in the number of chromosomes and ploidy changes. Through the analysis of the ploidy of T19-4 and T19-5, T19-4 and T19-5 were mostly triploid (excluding two pseudohybrid).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The induced F 1 by interspecies hybridization was obtained by induction selfing through F 1 egg cells [ 21 , 22 ], and there might be changes in the number of chromosomes and ploidy changes. Through the analysis of the ploidy of T19-4 and T19-5, T19-4 and T19-5 were mostly triploid (excluding two pseudohybrid).…”
Section: Discussionmentioning
confidence: 99%
“…Through cytological identification and FISH observation, it was found that hexaploid plants have about 54 chromosomes (2n = 6x ≈ 54, AAACCC) ( Figure 4 d), analyzing the source of hexaploid plants. Since the octoploid DH inducer was prone to producing aneuploid gametes [ 22 , 27 ], it was basically determined that it was the interspecific hybrid F 1 and the octaploid DH inducer hybridized which lost three A chromosomes. It was inferred that the octoploid plants in W59 were also interspecific crosses between F 1 and octoploid DH induction lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations